A comparison of discharge strategies after chemotherapy completion in pediatric patients with acute myeloid leukemia: a report from the Children's Oncology Group. Issue 7 (2nd July 2016) - Miller, Tamara P.; Getz, Kelly D.; Kavcic, Marko; Li, Yimei; Huang, Yuan-Shun V.; Sung, Lillian; Alonzo, Todd A.; Gerbing, Robert; Daves, Marla; Horton, Terzah M.; Pulsipher, Michael A.; Pollard, Jessica; et al.
Abstract: While most children receive acute myeloid leukemia (AML) chemotherapy as inpatients, there is variability in timing of discharge after chemotherapy completion. This study compared treatment-related morbidity, mortality and cumulative hospitalization in children with AML who were discharged after chemotherapy completion (early discharge) and those who remained hospitalized. Chart abstraction data for 153 early discharge-eligible patients enrolled on a Children's Oncology Group trial were compared by discharge strategy. Targeted toxicities included viridans group streptococcal (VGS) bacteremia, hypoxia and hypotension. Early discharge occurred in 11% of courses post-Induction I. Re-admission occurred in 80–100%, but median hospital stay was 7 days shorter. Patients discharged early had higher rates of VGS (adjusted risk ratio (aRR) = 1.67, 95% CI = 1.11–2.51), hypoxia (aRR = 1.92, 95% CI = 1.06–3.48) and hypotension (aRR = 4.36, 95% CI = 2.01–9.46), but there was no difference in mortality. As pressure increases to shorten hospitalizations, these results have important implications for determining discharge practices in pediatric AML.